204k views
0 votes
Prove that 2sin A/cos 3A + 2 sin3A/cos 9A +2sin9A/cos27A = tan 27A-tanA​

1 Answer

3 votes

Answer:

2 sin A / cos 3A + 2 sin 3A / cos 9A + 2 sin 9A / cos 27A = tan 27A - tan A

2 sin A/cos 3A

Multiply with cos A to Numerator and denominator

= 2 sin A cos A/cos 3A cos A

Formula (sin 2A = 2 sin A cos A)

= sin 2A / cos 3A cos A

Formula [ (sin a-b) / cos a cos b = tan a - tan b ]

So,

= sin 3A - A / cos 3A cos A

= tan 3A - tan A----> Equation 1

Apply same procedure we get

2 sin3A / cos 9A = tan 9A - tan 3A---> Equation 2

2 sin 9A / cos 27A = tan 27A - tan 9A----> Equation 3

Add Equation 1,2 and 3

tan 3A - tan A + tan 9A - tan 3A + tan 27A - tan 9A = tan 27A - tan A

2 sin A / cos 3A + 2 sin 3A / cos 9A + 2 sin 9A / cos 27A = tan 27A - tan A

Step-by-step explanation:

hope this helps

User Smokefoot
by
5.2k points